Early Pleistocene large mammals from Maka’amitalu, Hadar, lower Awash Valley, Ethiopia - Rowan, John (2022)
The Early Pleistocene was a critical time period in the evolution of eastern African mammal faunas, but fossil assemblages sampling this interval are poorly known from Ethiopia's Afar Depression. Field work by the Hadar Research Project in the Busidima Formation exposures (similar to 2.7-0.8 Ma) of Hadar in the lower Awash Valley, resulted in the recovery of an early Homo maxilla (A.L. 666-1) with associated stone tools and fauna from the Maka'amitalu basin in the 1990s. These assemblages are dated to similar to 2.35 Ma by the Bouroukie Tuff 3 (BKT-3). Continued work by the Hadar Research Project over the last two decades has greatly expanded the faunal collection. Here, we provide a comprehensive account of the Maka'amitalu large mammals (Artiodactyla, Carnivora, Perissodactyla, Primates, and Proboscidea) and discuss their paleoecological and biochronological significance. The size of the Maka'amitalu assemblage is small compared to those from the Hadar Formation (3.45-2.95 Ma) and Ledi-Geraru (2.8-2.6 Ma) but includes at least 20 taxa. Bovids, suids, and Theropithecus are common in terms of both species richness and abundance, whereas carnivorans, equids, and megaherbivores are rare. While the taxonomic composition of the Maka'amitalu fauna indicates significant species turnover from the Hadar Formation and Ledi-Geraru deposits, turnover seems to have occurred at a constant rate through time as taxonomic dissimilarity between adjacent fossil assemblages is strongly predicted by their age difference. A similar pattern characterizes functional ecological turnover, with only subtle changes in dietary proportions, body size proportions, and bovid abundances across the composite lower Awash sequence. Biochronological comparisons with other sites in eastern Africa suggest that the taxa recovered from the Maka'amitalu are broadly consistent with the reported age of the BKT-3 tuff. Considering the age of BKT-3 and biochronology, a range of 2.4-1.9 Ma is most likely for the faunal assemblage.